Substituent effects on the photophysical properties of tris(salicylideneanilines). Issue 2 (22nd December 2020) - Barboza, Cristina A.; Gawrys, Pawel; Banasiewicz, Marzena; Kozankiewicz, Bolesław; Sobolewski, Andrzej L.
Abstract : The role of the substitution of electron acceptor/donor groups on the photophysical properties of TSANs was investigated. The obtained results allow us to verify the dependence of the multiple emission bands on the functionalization of the TSAN core. Abstract : The role of electron acceptor/donor group substitution on the photophysical properties of tris(salicylideneanilines) (TSANs) was investigated. These compounds were synthesised and characterised through spectroscopic techniques including steady state absorption and emission spectroscopies. Their photochemical reaction mechanisms and properties were explored with the aid of ab initio methods of quantum chemistry. The obtained results allow us to verify the dependence of multiple emission bands on the substitution of electron donating and accepting groups to the tris(salicylideneaniline) core. The results also stress the differences in phosphorescence behaviour of TSANs for which this type of emission has not been reported so far.